Framing Medicine as a Moral Practice: An Introductory Medical School Course. (September 2018) - Allos, Ban Mishu; Yakes, Elizabeth Ann; Fleming, Amy; Cutrer, William B.; Pilla, Michael; Clair, Walter; Fowler, Michael; Miller, Bonnie
Abstract : Problem: The transition into medical school represents a time of profound professional development for medical students. Many medical schools manage this transition with brief orientations followed by abrupt moves into the anatomy laboratory. Recognizing that early introduction of key humanistic concepts could have a lasting impact on students' attitudes, faculty at the Vanderbilt University School of Medicine created the Foundations of the Profession (FoP) course to frame medicine as a moral practice. Approach: The FoP course, offered annually since 2012, occurs during the first week of medical school. Using coronary artery disease with a chief complaint of angina as a core example, teams of students create variations of five hypothetical patients and walk them through potential care episodes. This allows students to compare the impact of many factors on a provider's ability to uphold fundamental professional obligations. Students engage in readings, lectures, small-group discussions, clinic visits, and research on insurance plans. Faculty engage with students in small groups and establish a safe environment for discussion of challenging moral dilemmas. Outcomes: From 2013 to 2016, 356 (97%) of the 368 first-year medical students who took the course submitted summative course evaluations. Of the respondents, 349 (98%) indicated they believed the course contributed to their professional development and supported their learning. Next Steps: Future iterations of this course may include increased exposure to key educational faculty to solidify the formation of a moral scaffold on which to build subsequent knowledge. Abstract : Supplemental Digital Content is available in the text.